Systematic Design of a Pseudodifferential VCO Using Monomial Fitting - Dahl, Nicolai J.; Muntal, Pere L.; Andersen, Michael A. E. (Elektronika ir Elektrotechnika, 2023)
Digital integrated electronics benefits from its higher abstraction level, allowing optimisation methods and automated workflows. However, analogue integrated circuit design is still predominantly done manually, leading to lengthy design cycles. This paper proposes a new systematic design approach for the sizing of analogue integrated circuits to address this issue. The method utilises a surrogate optimisation technique that approximates a simple monomial function based on few simulation results. These monomials are convex and can be optimised using a simple linear optimisation routine, resulting in a single global optimal solution. We show that monomial functions, in many cases, have an analytic relation to integrated circuits, making them well suited for the application. The method is demonstrated by designing a 14 MHz pseudodifferential voltage-controlled oscillator (VCO) with minimised current consumption and is manufactured in a 180 nm process. The measured total current matches the predicted and is lower than that for other similar state-of-the-art VCOs.